Analisis Konsentrasi Nitrogen Dioksida (NO 2 ) Dan Sulfur Dioksida (So 2 ) dan Hubungannya Dengan Faktor Kelembaban udara dan kecepatan angin - Nurhayati; Ramli, Andi Yulianti (Fakultas Teknik - Universitas Satya Negara Indonesia, 2025)
Urban air pollution has become an issue that requires attention due to air pollution generating nitrogen dioxide (NO2) and SO2 gas. NO2 gas is a fairly dangerous pollutant for human health because it can cause eye irritation and lung discomfort, while SO2 gas can affect the cardiovascular system and cause headaches, low blood pressure, and rapid heartbeat. Therefore, it is necessary to monitor air quality while considering meteorological factors such as humidity and wind speed, which can lead to measurement errors. The average measurement of SO2 at the environmental laboratory location is 28.9 µg/m³, at the Villa Dago residential area the average is 24.2 µg/m³, NO2 gas at the environmental laboratory is 37.1 µg/m³ and at the Villa Dago residential area, the average is 26.8 µg/m³. The humidity at the environmental laboratory location averages 71.7 %RH and at the residential location averages 2.2 %RH. Meanwhile, the average wind speed is 2.0 m/s and the average at the villa Dago residential area is 2.2 m/s. The relationship between SO2 and humidity at the environmental laboratory location has an average correlation (r) of 0.76 with R2 of 0.5714, indicating that the sampling times at 7:00 AM, 1:00 PM, and 5:00 PM show strong correlation at the residential area around the environmental laboratory, with regression equation Y = 34.3 + 1.4x. Meanwhile, at the villa Dago residential area, the correlation (r) is 0.99, meaning there is a very strong relationship between the NO2 testing times, with R2 of 1 and regression equation Y = 26.4 + 0.2X.